EFEKTIVITAS FUNGI MIKORIZA ARBUSKULA DAN PUPUK P TERHADAP PERTUMBUHAN BIBIT LEDA (Eucalyptus deglupta Blume) DI MEDIA TANAH PASCA TAMBANG Effectiveness of Arbuscular Mycorrhizal Fungi and P Fertilizer on Seedling Growth of Leda (Eucalyptus deglupta Blume) - Ida Rosita; Sri Wilarso B.; Arum Sekar Wulandari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Leda (Eucalyptus deglupta) is one of fast growing species that prospecting for revegetation in post mined area. Leda is able to grow in poorly soil nutrient. The aim of this research is to analyze the effectiveness of AMF and P fertilizer on growth and P uptake of leda seedling. This research was conducted in split plot in Completely Randomize Design (CRD). The application AMF as a main plot consisted of 5 levels, namely M0 (control), M1(AMF from rubber plantation), M2 (AMF from primary forest), M3 (AMF from oil palm plantation), and M4 (AMF from natural rubber). The rock phosphate as subplot, consisted of three levels, such as 0 g P (P0), 2 g P (P1), and 5 g P (P2). The result showed that interaction between AMF from rubber plantation and 2 g of rock phosphate significantly gave the best effect for height and diameter of Leda while interaction between AMF-primary forest (M2) and P1 (2 g of rock phosphate) reach the best of the total dry weight. Both AMF from primary forest and oil palm plantation that combined with 2 g of rock phosphate give the best effect but was not significantly different for P uptake and P uptake efficiency.Key words: amf, growth, miychorrhiza, leda, p uptake, p efficiency